Efficient synthesis of spiroisoxazoline oxindoles - Ribeiro, Carlos J. A. (2013)
Acknowledgments: We thank Fundação para a Ciência e Tecnologia (Portugal) for financial support [Projects PTDC/QUI-QUI/111664/2009 and PTDC/SAU-FAR/110848/2009 and Fellowships SFRH/BD/69258/2010 and SFRH/BPD/44481/2008].